Combined algorithm of monolithic metal-dielectric filters designing - Bozhenko, Karina; Andrusenko, Evhen; Zadvornuy, Andriy (Видавництво Львівської політехніки, 2010)
In this paper we have combined algorithm calculations of monolithic metal-dielectric filters, based o the methods of classical synthesis, added the solutions optimization tasks of separate construction components determination.
Keywords: frequency filter; monolithic metal-ceramic filter